SPEECH ACT IN ROBERT ZEMECKIS MOVIE SCREENPLAY “FORREST GUMP” - Putra, Dimas Dwi; Sopha, Diana (Fakultas Sastra UMN AL Washliyah, 2024)
In this thesis entitled Speech Act in Robert Zemeckis Movie Screenplay